A Comparative Study of Pre-Service Teacher Education Programme at Secondary Stage in Bangladesh, India, Pakistan and Sri Lanka - Yadav, S. K. (INDIAN EDUCATIONAL REVIEW, 2011)
The comparative education is an analytical and synthetic approach. In the synthetic approach, it is seen to what extent the social structure, political philosophy and educational philosophy have influenced the educational system of a country. In such study, the totality of all situations and factors involved are kept in view. In other words, in comparative studies of education, now sociological bases are emphasised. Social process, social control, social organisation and social change of a country are carefully studied in comparative education, because it is believed that its educational system cannot be understood from teacher education point of view because it is a sub-system of education.